Investigation of contact stresses in engagement elements of screw conveyor safety clutch - Bulgakov, Volodymyr (2024)
In the article there is presented the design of a safety clutch for a screw conveyor with time-separated modes of slipping and axial displacement of the screw for automatic restoration of the operating condition in the event of overload. A calculation has been made using contact stresses in the engagement elements of the safety device, the level of which is the determining indicator that affects the wear rate of the contact surfaces. Using the SolidWorks Premium software diagrams of the distribution of contact stresses during operation of the safety clutch were constructed, by the results of which it was established that the analytical dependencies, presented in the article, can be used in the engineering design of various standard sizes of this protective mechanism.